Anesthetic Care for Orthopedic Patients: Is There a Potential for Differences in Care?. (March 2016) - Memtsoudis, Stavros G.; Poeran, Jashvant; Zubizarreta, Nicole; Rasul, Rehana; Opperer, Mathias; Mazumdar, Madhu
Abstract : Background: Differences in health care represent a major health policy issue. Despite increasing evidence on the mediating role of anesthesia type used for surgery on perioperative outcome, there is a lack of data on potential care differences in this field. The authors aimed to determine whether anesthesia practice (use of neuraxial anesthesia [NA] or peripheral nerve block [PNB]) differs by patient and hospital factors. Methods: The authors extracted data on n = 1, 062, 152 hip and knee arthroplasty procedures from the Premier Perspective database (2006 to 2013). Multilevel multivariable logistic regression models measured associations (odds ratios [ORs] and 95% CIs) between patient/hospital factors and NA or PNB use. Results: Of all patients, 22.2% (n = 236, 083) received NA and 17.9% (n = 189, 732) received PNB. Lower adjusted odds for receiving NA were seen for black patients (OR, 0.88; 95% CI, 0.86 to 0.91) and those on Medicaid (OR, 0.78; 95% CI, 0.74 to 0.82) or without insurance (OR, 0.89; 95% CI, 0.81 to 0.98). Furthermore, teaching hospitals (compared with nonteaching hospitals) had lower adjusted odds for NA utilization (OR, 0.35; 95% CI, 0.14 to 0.89). Although generally similar patterns were seen for PNB utilization, the main difference was that particularly Hispanic patients were less likely to receive PNB compared with white patients (OR, 0.60; 95% CI, 0.56 to 0.65). Sensitivity analyses generally validated our results. Conclusions: Significant differences exist in the provision of regional anesthetic care with factors such as race and insurance type being important determinants of anesthetic practice. Further and in-depth research is needed to fully assess the background of these differences. Abstract : In a review of more than 1 million hip and knee arthroplasty procedures in the Premier Perspective database, use of neuraxial anesthesia was considerably less (odds ratio [OR], 0.35) in teaching versus nonteaching hospitals and moderately less for black patients (OR, 0.88), those on Medicaid (OR, 0.78), and those without insurance (OR, 0.89).